ASPEK TANGIBLE DAN INTANGIBLE KOTA SEBAGAI ASPEK PENDUKUNG PENCITRAAN KOTA SOLO - Marwanto, Aries Budi (Institut Seni Indoensia Surakarta, 2010)
The study entitled â€œIMAGE STRATEGY OF SOLO AS A CITY OF CULTUREâ€ includes excavation of a city image that is communicated through marketing efforts. Image of the city includes aspects of artifacts (tangible) and values (intangible). Excavation of the two aspects of imaging supports Solo as a City of Culture.Tangible aspects of the city of Solo is quite diverse as palaces, villages, buildings,temples, reservoirs, recreation areas, plateaus and many interesting sights to visit. Intangible cultural heritage, among others in the field - a field as follows oral traditions and expressions, including language; performing arts; social customs, rites, and celebrations - celebrations; knowledge and practices about nature and behavior of the universe; and traditional craft skills. Keywords: Strategy, image, city.